‘What we do now is provide service which may be irrelevant to our clients’ Imagining career resilience research and training from an indigenous knowledge production perspective - Ebersöhn, Liesel (South African Journal of Higher Education, 2016)
More often than not, higher education curricula expound Western-oriented epistemologies of psychology. Trained psychologists may thus not be appropriately equipped to provide career counselling that is suitable to a resource-scarce environment, nor enriched with a heritage of knowledge related to customary career resilience practices. Rather than enabling clients, one could argue that existing career counselling training, and subsequent practice, may in fact hinder clients’ ability to adapt and flourish in their (career-)lives. The thesis of this article is that an indigenous knowledge production imperative affords a way in which embedded values, practices, patterns and concepts synonymous with career resilience in South Africa can be documented systematically. Indigenous knowledge production urges researchers to appreciate what lies at the heart of everyday occurrences (such as career decision making), and be familiar with what is embedded in long-standing habits, rituals and patterns (related to, for example, career choice). In this regard I discuss both indigenisation and establishing an indigenous psychology as research schemas to develop ecologically-just curricula for higher education training. I explain the epistemological premises of indigenous knowledge production and present research strategies framed within indigenous knowledge production.